2020
DOI: 10.1016/j.aml.2020.106387
|View full text |Cite
|
Sign up to set email alerts
|

The monoatomic FPU system as a limit of a diatomic FPU system

Abstract: We consider a diatomic infinite Fermi-Pasta-Ulam (FPU) system with light and heavy particles. For a small mass ratio, we prove error estimates for the approximation of the dynamics of this system by the dynamics of the monoatomic FPU system. The light particles are squeezed by the heavy particles at the mean value of their displacements. The error estimates are derived by means of the energy method and hold for sufficiently long times, for which the dynamics of the monoatomic FPU system is observed. The approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Physically, this means that the mass-less particles are fixed halfway between the heavier ones, corresponding with the intuition developed in [38,56]. Upon setting…”
Section: Introductionmentioning
confidence: 82%
“…Physically, this means that the mass-less particles are fixed halfway between the heavier ones, corresponding with the intuition developed in [38,56]. Upon setting…”
Section: Introductionmentioning
confidence: 82%
“…This paper is, in part, an attempt to address similar issues for the Cauchy problem. We also mention the article by Pelinovsky and Schneider 9 . In that paper, the authors treat a diatomic FPUT lattice in the limit that the mass ratio tends to zero.…”
Section: The Problemmentioning
confidence: 99%
“…Remark As we mentioned in the introduction, the article 9 treats the monatomic limit of a diatomic FPUT lattice in the case of small mass ratio. Their mass ratio is named ε2 and is most comparable to our internal mass μ.…”
Section: The Leading Order Fput Approximationmentioning
confidence: 99%
“…We mention just a handful of related results here and discuss others in the context of future problems in Section 5. Pelinovsky‐Schneider 25 considered the dimer small mass limit as an initial value problem in 2(Z)$\ell ^2(\mathbb {Z})$‐type sequence spaces and found that if the initial data are close to a solution of the limiting monatomic lattice and the mass ratio is sufficiently small, then the dimer solution remains close to that monatomic solution. McGinnis and Wright 26 moved well beyond the polyatomic regime to find that the classical wave equation is a good approximation for linear FPUT lattices with “random” material data, that is, their potentials are Vj(r)=κjr$\mathcal {V}_j^{\prime }(r) = \kappa _jr$, where κj$\kappa _j$ and the masses mj$m_j$ are all random variables.…”
Section: Introductionmentioning
confidence: 99%